Analisis Komparatif Perspektif KHI dan Fiqih Imam Syafi’i tentang Hukum Ihdad bagi Perempuan - Ulum, Hairul (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2018)
Abstract The article discusses the comparison of Ihdad provision between KHI and Imam Syafi’i. KHI states that Ihdad must be done during ‘iddah for wives left by their husband due to death as a symbol of grief and avoiding slender. These wives, according to Imam Syafi’i, must do Ihdad in case they are adults, children, kafir dzimmis, or slaves. The distinctive is also found in the law consequence that should be accepted during Ihdad. In KHI there is no law that sets things forbidden during Ihdah in details as Imam Syafi’i’s fiqh provision. Keywords : KHI, Fiqh, Ihdad Law.